KOMPETENSI BERBICARA PRAMUWISATA ARAB DI INDONESIA (STUDI KASUS DI KAWASAN PUNCAK) - Misran, Misran (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
Speaking is the most frequently used language competence for tourist guides. They use this competence in order to serve their guests optimally. This study aims to examine Arabic speaking competence of tourist guides in Puncak, West Java. This study uses a qualitative approach with various data collection techniques including participatory observation, indirect observation, and interviews with a number of key informants. The key informants in this research are tourist guides, tourist guide association committee, and tour operators in Puncak area. This study found that language acquisition methods affect the speaking competence of the tourist guide, which may increase over time depending on the intensity of interaction with tourists and language usage. These tourist guides show different levels of language proficiencies including grammar accuracy, different ability to avoid using slang, and involvement in various topics of conversation. Self-taught guides normally have limited abilities in almost all of the above indicators, while guides who studied Arabic either formally or semi-formally tend to be more competent although they cannot avoid using Arabic slang. Meanwhile, guides who learned Arabic from their interactions with native speakers tend to ignore grammar and language accuracy even though they are able to communicate effectively.